Examining veteran housing instability and mortality by homicide, suicide, and unintentional injury. Issue 2 (3rd July 2021) - Cusack, Meagan; Montgomery, Ann Elizabeth; Cashy, John; Dichter, Melissa; Byrne, Thomas; Blosnich, John R.
ABSTRACT: To examine the relationship between Veterans' housing instability and mortality by homicide, suicide, and unintentional injury, this retrospective study examined administrative data from Veterans Health Administration (VHA) patients who responded to the Homelessness Screening Clinical Reminder (HSCR) between October 1, 2012 and September 30, 2016 and were searched through the National Death Index (NDI) for date and cause of death (N = 5, 850, 044). Analyses calculated survival time and compared mortality for three groups—(1) stably housed Veterans, (2) unstably housed Veterans, and (3) Veterans at imminent risk for housing instability—using adjusted Cox proportional hazards models. Stably housed Veterans had a significantly longer median survival time (3.3 years) than unstably housed Veterans and those at imminent risk for housing instability (2.5 and 2.6 years, respectively). Unstably housed Veterans and those at imminent risk for housing instability had greater risk of all-cause mortality (Adjusted Hazard Ratio [aHR] = 1.69 and 1.48, respectively) and of dying by homicide (aHR = 3.01 and 2.65, respectively), suicide (aHR = 1.75 and aHR = 1.80, respectively), and unintentional injury (aHR = 3.13 and aHR = 1.92, respectively) compared with stably housed Veterans. More proactive measures are needed to prevent external causes of mortality among Veterans who are unstably housed or at imminent risk for housing instability.